South Africa’s Challenges Pertaining to Mine Closure — The Concept of Regional Mining and Closure Strategies - van Tonder, DM; Coetzee, H; Esterhuyse, S; Msezane, N; Strachan, L; Wade, P; Mafanya, T; Mudau, S (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
The South African Department of Minerals and Energy (DME) initiated the Sustainable Development Through Mining (SDM) initiative in 2005 to develop and implement a strategy for sustainable development in the mining sector, with a view to reporting, in terms of the Johannesburg Plan of Implementation (JPI), to the United Nations in 2010 on the sector’s sustainability goals. This initiative has generated, and supports, a variety of projects under its sustainability banner, including some specifically orientated towards mine closure and its variegated dimensions and implications. The specific focus area of this paper is the development of the concept of regional mining and closure strategies to deal with closure challenges where mines have an inter-connected and/or an integrated environmental impact, for instance the gold mining areas within the Witwatersrand mining basins of South Africa. Regional mining and closure strategies present an innovative departure from past regulatory closure approaches. The paper moves on to consider further policy and legislative interventions necessary for mine closure in such circumstances and outlines proposed strategies to address these.